The Historical Roots and Identities of Local Strongmen Groups in Indonesia - Yanwar Pribadi (Kawalu: Journal of Local Culture, 2015)
This paper deals with the historical roots and identities, nature and characteristics of local strongmen groups in Indonesia, and aspects of violence in Indonesia. In the rural colonial Java, there were rampok-bandits and jago groups; whereas today in Banten there are jawara groups and elsewhere in Indonesia people commonly recognized preman groups. In this paper I will focus on these four groups: rampok-bandits (or bandits), jago, jawara, and preman. These groups are parts of the long-established strongmen groups that have characterized Indonesian history. Among the questions addressed are: what is the origin and what are the characteristics of local strongmen groups in society? How does violence embody in the way of life of local strongmen groups? What is their position in society? How do they characterize local cultures in their place of origin? Keywords: Rampok-bandits, Jago, Jawara, Preman, Violence